Profitability of Islamic commercial banks using explanatory third party funds, capital adequacy and non-performing finance. - Tsmara Zain, Asil; Muthohar, Ahmad Mifdlol (Islamic Accounting Journal, 2024)
Objective & object: The purpose of this study was to analyze the effect of Third Party Funds, Capital Adequecy, and Non Perfoming Financing on the Profitability of Islamic Commercial Banks with Mudharabah Financing as a Moderating Variable, the sample used in this study was BUS registered in OJK and Bank Indonesia in the period 2018-2022. Methods: The methods used in this research are descriptive analysis, stationarity test, classical assumption test, moderate regression analysis. The tools used in this test use eviews statistical software. Results & Conclusions: Contains the results of testing using the method presented in the method section. Limitations: This section is not a weakness of the researcher, but contains research weaknesses that were not carried out because they were beyond the control of the researcher. Implications: Contains follow-up on research results and research limitations. Research results can be followed up practically and academically. Limitations can be suggested for further research.